Peculiarities of blockchain tech use in international business and finance - Makarenko, Anastasiya B.; Shyriaieva, N. V. (Одеський національний економічний університет, 2020)
In the abstracts peculiarities of blockchain technologies use in international business and finance are considered. It seems that the Industry 4.0 touches all spheres of business environment as well as a government. To handle the block chains the risks and benefits should be taken into consideration.
Keywords: blockchain; business environment; finance; international business